2005
DOI: 10.3109/s10165-005-0411-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between initial clinical manifestation and long-term prognosis of patients with systemic lupus erythematosus

Abstract: The relationship between clinical manifestations and prognosis was examined and evaluated among systemic lupus erythematosus (SLE) patients. A total of 542 patients with SLE were selected and divided into nine groups according to their main clinical manifestation at the time of initial diagnosis. The relationship between these clinical manifestations and long-term prognosis was evaluated in respect to the survival, remission, relapse rates, the development of a new clinical manifestation, and/or damage index. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Our previous study first demonstrated the efficacy in Japanese patients, and these results were related to the lymphocyte marker (7). However (10), as patients with no nephritis at the time of the initial diagnosis and who had nephritis during the disease course. These initial main manifestations were defined in our previous study (10 …”
Section: Intravenous Cyclophosphamide (Ivcy) Therapy Has Been Acceptementioning
confidence: 93%
See 1 more Smart Citation
“…Our previous study first demonstrated the efficacy in Japanese patients, and these results were related to the lymphocyte marker (7). However (10), as patients with no nephritis at the time of the initial diagnosis and who had nephritis during the disease course. These initial main manifestations were defined in our previous study (10 …”
Section: Intravenous Cyclophosphamide (Ivcy) Therapy Has Been Acceptementioning
confidence: 93%
“…However (10), as patients with no nephritis at the time of the initial diagnosis and who had nephritis during the disease course. These initial main manifestations were defined in our previous study (10 …”
Section: Intravenous Cyclophosphamide (Ivcy) Therapy Has Been Acceptementioning
confidence: 99%
“…Childhood-onset SLE is often associated with major organ involvement, including neuropsychiatric disease (NPSLE) affecting between 43% and 95% of patients (1,2). Although it is a risk factor for poor disease outcomes in all age groups (3)(4)(5)(6)(7)(8), NPSLE is of special concern in pediatric populations. Children with NPSLE may experience school failure due to attention and learning difficulties (9).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the presence of brain MRI abnormalities significantly increased the mortality in patients with diffuse NPSLE [16]. Among a variety of manifestations in diffuse NPSLE, ACS is the most serious one, sometimes resulting in poor prognoses [10,17]. However, there was no significant association of brain MRI abnormalities with certain types of diffuse NPSLE [16].…”
Section: Discussionmentioning
confidence: 91%
“…The frequency of ACS ranges from 50% to 58% of patients with diffuse NPSLE [15,16]. Among a variety of manifestations in NPSLE, ACS is the most serious one, requiring extensive immunosuppressive therapy and sometimes resulting in poor prognosis [17,18].…”
Section: Introductionmentioning
confidence: 99%